O direito fundamental à razoável duração do processo e o dever de eficiência do Poder Judiciário - reflexões sobre um caso concreto: a 10ª vara da Seção Judiciária Federal do Estado do Ceará no quinquênio 2005/2010 - Lima, Alcides Saldanha (2011)
This study aims , in view of the pair make concrete effort fundamental rights and effective judicial functions , investigas the legal and practical consequences of the insertion in the Constitution of 1988 the right to reasonable length of judicial proceedings (Article 5 , LXXVIII - Constitutional Amendment No. 45/2004 ) and its relation to the previous insertion of the principle of administrative efficiency (Article 37 , caput - Constitutional Amendment 19/1998 ).